PENTINGNYA KETERLIBATAN MASYARAKAT DALAM PENCEGAHAN TINDAK PIDANA LINGKUNGAN HIDUP - Manik, Sri Elviana; Hasibuan, Nursaidah; Rahmi, Mauliza (PT Metrum Karya Mandiri, 2024)
The environment is the most important thing for the survival of society, therefore there needs to be special attention to preserving the environment, so protecting the environment is not only the role of the authorities or people concerned with environmental services but is the responsibility of the entire community. The community's right to the environment actually includes the obligation to participate in environmental maintenance and protection in the law, article 70 paragraph 1 of the Environmental Protection and Management Law (UUPPLH) confirms that the community has the right to environmental management and protection. The aim of this research is to find out what the rights and obligations are, as well as the extent of the community's role if an environmental crime occurs. This research uses normative research by analyzing it based on literature studies, journals, essays and official websites, showing that society has obstacle factors such as legal means, facilities and means, also including public legal awareness of the environment. This research found that community participation is important in environmental protection and management procedures. However, currently there are still concerns regarding the environmental impact and the principles of openness and community involvement. Involving the community is key in the strategy to prevent environmental crimes, because it is one of the efforts to increase public awareness of the importance of preserving the environment.